INVENTARISASI JENIS ANGGREK (ORCHIDACEAE) TERESTRIAL DI TAMAN WISATA ALAM BUKIT KELAM KABUPATEN SINTANG - Lestari, Lulu Dwi; Rafdinal, Rafdinal; Mukarlina, Mukarlina (Universitas Tanjungpura, 2019)
Bukit Kelam Nature Tourism Park in Sintang District is a nature conservation area that has become the habitat for a wide range of endemic flora in West Kalimantan. This study aimed to identify terrrestrial orchids (Orchidaceae) species in Bukit Kelam Nature Tourism Park in Sintang District. This study was conducted from September to November 2017. The inventory of orchids specieswas done by the cruise method. The study obtained 12 terrestrial orchid species i.e Arundina graminifolia, Bromheadia finlaysoniana, Corybas pictus, Coelogyne kelamensis, Dendrobium lobii, Dendrobium olivaceum, Dipodium pictum, Liparis sp., Paphiopedilum bullenianum, Plocoglottis lowii, Spathoglottis kimbaliana,and Thrixspermumamplexicaule.